(untitled) (Journal Of Educational and Psychological Researches, 2024)
This paper aims to verify the effectiveness of a gamification-based enrichment program in developing EFL creative writing skills (fluency, flexibility, originality, and elaboration) among third intermediate grade students. The researcher adopted the quasi-experimental method (one-group pretest-posttest design) and applied a validated test of creative writing skills in short stories and a validated gamification-based enrichment program, including a teacher’s manual and textbook, to a sample of (20) third intermediate grade students of the intermediate school at Princess Nourah bint Abdulrahman University in the second semester of 2021/2022. The results showed a statistically significant difference between the mean scores of the experimental group in the pre-test and post-test of creative writing skills in fluency, flexibility, originality, and elaboration, as well as the total score in favor of the post-test due to the gamification-based enrichment program. The effect size of the gamification-based enrichment program on developing the EFL creative writing skills among third intermediate grade students was high in each skill and the overall score, suggesting the effectiveness of the program. Therefore, the reseaercher recommended utilizing and implementing the gamification-based enrichment program to equip intermediate stage students with EFL creative writing skills.